Down-regulation of the cyclin E1 oncogene expression by microRNA-16-1 induces cell cycle arrest in human cancer cells - Wang, Fu; Fu, Xiang-Dong; Zhou, Yu; Zhang, Yi (BMB reports, 2009)
Cyclin E1 (CCNE1), a positive regulator of the cell cycle, controls the transition of cells from G1 to S phase. In numerous human tumors, however, CCNE1 expression is frequently dysregulated, while the mechanism leading to its dysregulation remains incompletely defined. Herein, we showed that CCNE1 expression was subject to post-transcriptional regulation by a microRNA miR-16-1. This was evident at protein level of CCNE1 as well as its mRNA level. Further evident by dual luciferase reporter assay revealed that two evolutionary conserved binding sites on 3' UTR of CCNE1 were the direct functional target sites. Moreover, we showed that miR-16-1 induced G0/G1 cell cycle arrest by targeting CCNE1 and siRNA against CCNE1 partially phenocopied miR-16-1-induced cell cycle phenotype whereas substantially rescued anti-miR-16-1- induced phenotype. Together, all these results demonstrate that miR-16-1 plays a vital role in modulating cellular process in human cancers and indicate the therapeutic potential of miR-16-1 in cancer therapy.